Factors that influence an individual’s decision to undergo bariatric surgery: A qualitative systematic review - Natasha Keogh; Dawn Horsom; Geraldine Lee; Mohamad M. Saab (PLoS ONE, 2025)
Introduction Obesity is a significant health issue associated with chronic conditions such as cardiovascular disease and type 2 diabetes. Bariatric surgery is the most effective weight loss treatment for obesity. This systematic review aimed to examine factors influencing individuals’ decisions to undergo bariatric surgery. Methods This systematic review was guided by the JBI Manual for Evidence Synthesis for Qualitative Reviews and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. Literature searches were conducted in CINAHL, PubMed, Cochrane Library, APA PsycINFO, and APA PsycArticles. Results were analysed using a meta-aggregative approach. Quality appraisal was conducted using the JBI Checklist for Qualitative Research. Results Thirteen studies were included. Health concerns, fears of obesity-related comorbidities, and a desire to improve physical health and quality of life emerged as key motivators to undergoing bariatric surgery. Support from healthcare professionals and family played a crucial role in motivating individuals to consider surgery. Women particularly noted concerns about fertility as a motivator to undergo bariatric surgery. Disclosure of surgery, financial concerns, transport, family and work commitments, and perceived risks of surgery were identified as barriers to undergoing bariatric surgery. Conclusion Findings highlight the need for healthcare professionals to adopt empathetic, patient-centred approaches when discussing bariatric surgery. Addressing financial, insurance, and logistical barriers, alongside stigma and family resistance, is essential. Improving patient education, strengthening provider relationships, and offering tailored support can enhance decision-making, access, and long-term outcomes for those considering bariatric surgery.